2010
DOI: 10.1039/c004745g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free tandem reaction in water: An efficient and regioselective synthesis of 3-hydroxyisoindolin-1-ones

Abstract: A mild and effective method was developed for the construction of heterocyclic building blocks 3-hydroxyisoindolin-1-ones via a metal-free tandem transformation with excellent regioselectivity. Significantly, the strategy presents an atom-economical and environmentally friendly transformation, in which two new C-N bonds and one C-O bond are formed in water from two simple starting materials. Moreover, a broad spectrum of substrates can participate in the process effectively to produce the desired products in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…2,3-Dibenzyl-3-hydroxyisoindolin-1-one (3 a) [21] Colorless crystals, 66 %, m.p. 164 8C; 1 146.3, 138.6, 134.9, 131.8, 131.0, 130.6, 129.6, 128.6, 128.5, 128.0, 127.4, 127.1, 131.7, 131.7, 91.5, 44.1, 42.5 1, 147.0, 138.9, 135.3, 132.0, 131.5, 131.2, 129.8, 129.0, 128.1, 128.0, 128.0, 126.6, 123.1, 122.0, 91.1, 42.8, 42.3, 54.8 23 H 21 NO 2 :C ,8 0.44;H ,6 .16;N ,4.08.…”
Section: Generalp Rocedure For the Photodecarboxylation Including Conmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3-Dibenzyl-3-hydroxyisoindolin-1-one (3 a) [21] Colorless crystals, 66 %, m.p. 164 8C; 1 146.3, 138.6, 134.9, 131.8, 131.0, 130.6, 129.6, 128.6, 128.5, 128.0, 127.4, 127.1, 131.7, 131.7, 91.5, 44.1, 42.5 1, 147.0, 138.9, 135.3, 132.0, 131.5, 131.2, 129.8, 129.0, 128.1, 128.0, 128.0, 126.6, 123.1, 122.0, 91.1, 42.8, 42.3, 54.8 23 H 21 NO 2 :C ,8 0.44;H ,6 .16;N ,4.08.…”
Section: Generalp Rocedure For the Photodecarboxylation Including Conmentioning
confidence: 99%
“…8,138.8,131.7 ( 3 J F,C = 7.70 Hz),131.6,131.4,131.2,129.1,128.0,128.0 126.6,123.1,122.0,114.2 ( 2 1, 146.7, 138.8, 134.2, 131.7, 131.7, 131.2, 131.2, 129.2, 128.0, 128.0, 127.4, 126.6, 123.1, 122.1, 90.8, 42.4, 42.2 1, 146.7, 138.8, 134.6, 132.1, 131.6, 131.1, 130.3, 129.2, 128.0, 128.0, 126.6, 123.1, 122.1, 119.7, 90.7, 42.4, 42.2 ,4 .44;N ,3 .43. Found:C ,6 4.82;H ,4 .45;N ,3.40. 2-Benzyl-3-(4-methoxybenzyl)-3-hydroxyisoindolin-1-one (3 f) [21] Colorless crystals, 73 %, m.p. 160 8C; 1 HNMR (300 MHz, CDCl 3 ) d 2, 157.7, 147.1, 138.8, 131.5, 131.3, 131.0, 129.0, 128.0, 128.0, 127.0, 126.6, 123.2, 122.1, 112.9, 91.1, 54.8, 42.4, 42.3 23 H 21 NO 3 :C ,7 6.86;H ,5.89;N ,3.90.…”
Section: Generalp Rocedure For the Photodecarboxylation Including Conmentioning
confidence: 99%
“…In 2010, Zhou and coworkers reported a promising method which realized the construction of 3-hydroxyisoindolinones from 2-(phenylethynyl)benzoic acids and alkyl amines catalyzed by Bu 4 N + OAc À . [17] Recently, transition-metal-catalyzed tandem reactions of acetophenones [18] or benzamides [19] offer an efficient access to 3-hydroxyisoindolinones. However, their values are reduced by the employment of expensive metal catalysts, which causes metal contamination of the products as well.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported methods for the synthesis of 3hydroxyisoindolinones, what seems particularly interesting is the Bu 4 N + OAc À catalyzed two-step one-pot protocol developed by Zhou and coworkers (Scheme 1a). [17] They revealed that the alkyne moiety of 2-alkynylbenzoic acids I could be activated by a catalytic amount of Bu 4 N + OAc À to be attacked by the carboxyl group to form the enol lactone II at 100°C under microwave irradiation in the first step. Then the amines, which are added in the second step, could attack the enol lactone II to give the 3-hydroxyisoindolinones III in good to high yields.…”
Section: Introductionmentioning
confidence: 99%
“…Under microwave heating, a mild and effective method for the construction of 3-hydroxyisoindolin-1-ones via a metal-free tandem transformation using a phase transfer catalyst proceeded in good yields with excellent regioselectivity (Scheme 21). The strategy presents an atom-economical and environmentally friendly transformation, in which one C-O bond and two new C-N bonds are formed in water from two simple starting materials (Zhou, Y. et al, 2010).…”
Section: Aqueous Microwave Synthesismentioning
confidence: 99%